Analisa Pengaruh Kuat Arus Terhadap Kekuatan Tarik Dan Bending Sambungan Las Kampuh V Menggunakan Las SMAW Dengan Elektroda E6013 Pada Pengelasan Baja Karbon Rendah - Ridwan, Ridwan; Kadir, Abd.; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2021)
Strong current in welding is something that has always been a problem in the welding process. High currents can cause penetration of the welded material, whereas low currents can cause shallow penetration. The purpose of the study was to determine the effect of current on the tensile and bending strength of V seam welded joints using SMAW welding with E6013 electrodes on low carbon steel welding. The research method used is to make a seam on a steel plate with an angle of 60 degrees and then weld it with a different current. The current used is 70, 90, 110 amperes with an electrode diameter of 2.6 mm. The samples that have been welded are then formed into tensile and bending test specimens. The results showed that the highest average tensile stress was 518.310 MPa at a welding current of 110 amperes. The highest average tensile strain is 34.00% at a welding current of 70 amperes. The highest average elastic modulus is 0.01864 GPa at a welding current of 110 amperes. For bending testing at 70 amperes, the fb1 specimen has cracks in the weld metal area with a crack length of 1.00 mm and the fb2 specimen has 0.50 mm cracks, while the 90 amperes fb1 specimen has 1.00 mm cracks, and fb2 specimens have 0.50mm crack. Current 110 amperes fb1 specimen has a crack of 4.70 mm, and fb2 specimen has a crack of 3.00 mm. From the results of the study, a good welding current for a plate with a thickness of 7.5 mm with an E6013 electrode with a diameter of 2.6 mm is at a current of 90 amperes.